2021
DOI: 10.1016/j.isci.2021.103170
|View full text |Cite
|
Sign up to set email alerts
|

Excipient of paclitaxel induces metabolic dysregulation and unfolded protein response

Abstract: Summary Taxane-based reagents, such as Taxol, Taxotere, and Abraxane, are popular anti-cancer drugs that can differ in their clinical efficacy. This difference is generally attributed to their active pharmaceutical ingredients. Here, we report a serendipitous discovery that Taxol induces metabolic dysregulation and unfolded protein response. Surprisingly, these effects of Taxol are entirely dependent on its excipient, Cremophor EL (CrEL). We show that CrEL promotes aerobic glycolysis and in turn res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In previous studies, it has been reported that chemotherapeutic agents, such as paclitaxel and platinum-based drugs, disrupt lipid homeostasis both in human and mice ( 62 , 70 ). Our study is the first to highlight the role of lacteal junction in lipid malabsorption in a chemotherapy-induced cachexia mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been reported that chemotherapeutic agents, such as paclitaxel and platinum-based drugs, disrupt lipid homeostasis both in human and mice ( 62 , 70 ). Our study is the first to highlight the role of lacteal junction in lipid malabsorption in a chemotherapy-induced cachexia mouse model.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Moreover, ANGPTL4 is upregulated due to Cremophor EL, which promotes aerobic glycolysis and triggers proinflammatory gene expression and caspase/gasdermin E-dependent pyroptosis. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Dai et al have reported that paclitaxel induces aerobic glycolysis and hypertriglyceridemia ( Dai et al, 2021 ). These metabolic effects are proposed to be linked with the excipient CrEL, which is unique to paclitaxel as compared with other taxane-containing chemotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel, which is hydrophobic, is formulated with CrEL, which enhances drug solubility ( Scripture et al, 2005 ). Dai et al demonstrated patients with breast cancer developed higher triglyceride levels in the group that received paclitaxel with CrEL, compared to abraxane (nanoparticle albumin-bound paclitaxel), docetaxel and non-taxanes ( Dai et al, 2021 ). There was a triglyceride increase in all four groups, however in the paclitaxel with CrEL group, 8% developed triglyceride concentrations above 131 mg/dL (3.4 mmol/L ) and 44% demonstrated a 70% rise in triglycerides after this therapy.…”
Section: Discussionmentioning
confidence: 99%